A Sociocultural Exploration of EFL Teachers’ Beliefs about Formative Assessment in Indonesia - Nufus, Hayatun; Aziz, Zulfadli Abdul; Muthalib, Kismullah Abdul (Journal of English Language Teaching Innovations and Materials (Jeltim), 2025)
While previous studies have examined formative assessment in various contexts, limited attention has been given to how English teachers in Indonesia’s “Emancipated Curriculum” interpret and implement it within sociocultural frameworks. This study employed a qualitative descriptive design to explore the beliefs of two English teachers at a non-mover school in Banda Aceh through the lens of Vygotsky’s Sociocultural Theory and Black and Wiliam’s formative assessment framework. Data were collected through semi-structured interviews, classroom observations, and document analysis. The findings revealed two contrasting belief orientations shaped by teaching experience and institutional support. The experienced teacher demonstrated a strong understanding of formative assessment grounded in sociocultural principles such as scaffolding and feedback within the Zone of Proximal Development (ZPD). Conversely, the novice teacher perceived assessment mainly as a tool for measuring performance, showing limited engagement in interactive or collaborative practices. Both acknowledged the importance of formative assessment but faced barriers related to time, resources, and training. The study highlights the influence of sociocultural factors on teacher beliefs and calls for continuous professional development and digital integration to foster equitable and effective learning environments. How to cite this paper: Nufus, H., Aziz, Z. A., & Muthalib, K. A. (2025). A sociocultural exploration of EFL teachers’ beliefs about formative assessment in Indonesia. Journal of English Language Teaching Innovations and Materials (Jeltim), 7(2), 80–105. https://doi.org/10.26418/jeltim.v7i2.96419